Mild cognitive impairment (MCI) and dementia in a sample of adults in the city of Bogotá (2017)
The low prevalence of dementia described in communities is likely due to the low sensitivity of screening tests and an absence of evaluation by specialists. Objective: To estimate the prevalence of mild cognitive impairment (MCI) and dementia in adults older than 50 years. Methods: A two-phase, cross-sectional study was conducted by specialists to evaluate cognition and associated demographic risk factors in 1,235 independent community-dwelling adults from Bogotá. In Phase I, screening was performed using the MMSE and MoCA tests. In Phase II, after application of a comprehensive neuropsychological battery with neurologic and psychiatric evaluations, a cognitive diagnosis was established by consensus. Results: The prevalence found for MCI was 34% and for dementia was 23%. MCI was associated with incomplete high school, OR=1.74 (95%CI=1.23-2.45), and with an age of 70-79 years, OR=1.93 (95%CI=1.47-2.53). A total of 73% of MCI cases were amnestic. Dementia was associated with incomplete primary education, OR=8.98 (95%CI=5.56-14.54), complete primary education, OR=6.23 (95%CI=3.70-10.47), and age older than eighty years, OR=3.49 (95%CI=2.23-5.44). Conclusion: The prevalence of dementia found was greater than the rates reported in previous studies. Low educational level was the main risk factor for cognitive impairment and should be considered in strategic planning for the local health system.